2022
DOI: 10.3390/membranes12070638
|View full text |Cite
|
Sign up to set email alerts
|

Wicking in Porous Polymeric Membranes: Determination of an Effective Capillary Radius to Predict the Flow Behavior in Lateral Flow Assays

Abstract: The working principle of lateral flow assays, such as the widely used COVID-19 rapid tests, is based on the capillary-driven liquid transport of a sample fluid to a test line using porous polymeric membranes as the conductive medium. In order to predict this wicking process by simplified analytical models, it is essential to determine an effective capillary radius for the highly porous and open-pored membranes. In this work, a parametric study is performed with selected simplified structures, representing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Capillary rise time, a requirement set by the manufacturer for nitrocellulose membranes, is the period needed for a fluid front to pass through a membrane with a 40 mm width. The kinetics and rate of assay development are crucial, and the selected wicking rate will have a significant impact on the sensitivity and effectiveness of the test [ 64 , 65 ].…”
Section: Principle Of Lfamentioning
confidence: 99%
“…Capillary rise time, a requirement set by the manufacturer for nitrocellulose membranes, is the period needed for a fluid front to pass through a membrane with a 40 mm width. The kinetics and rate of assay development are crucial, and the selected wicking rate will have a significant impact on the sensitivity and effectiveness of the test [ 64 , 65 ].…”
Section: Principle Of Lfamentioning
confidence: 99%
“…reported that 44 LFAs were authorized by the FDA in the USA for COVID-19 in vitro diagnostics. Simply, an LFA can be described as a system consisting of an analytical membrane that act as an autarkic microfluidic pump system capable of transporting the pretreated (if necessary) sample from the sample pad to conjugate pad [ 7 ]. While diffusing through the conjugate pad, the sample is mixed with gold nanoparticles (AuNPs), biomolecule conjugates, and additives, which react with the antibodies on the membrane [ 4 , 7 ] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Lucas and Washburn derived a solution for porous mediums, considering the capillary pressure developed in a cylindrical capillary with the assumption that the porous medium is a collection of cylindrical capillaries [ 15 ]. Altschuh et al [ 7 ] demonstrated that the estimated effective pore radius is approximately eight to ten times higher than the geometric means. They argued that use of solutions such as the Young–Laplace equation and Lucas and Washburn solutions are not applicable in the context of membranes, as the structures are often non-axisymmetric and closed.…”
Section: Introductionmentioning
confidence: 99%
“…However, real microstructures do not always ensure periodicity, except for few cases, such as crystal structures. In particular, when extracting a representative element from reference experimental data [3][4][5], such as computer tomography images, the representative volume element is typically cropped from a larger network. This cropping process often results in the truncation of boundaries, introducing non-periodic features into the extracted element.…”
Section: Introductionmentioning
confidence: 99%